Pemberdayaan Masyarakat Melalui Inovasi Desain Kandang Ayam Bahagia Mendukung Ketahanan Pangan Keluarga - Nurfuady, Ijtihad; Warnaen, Andi; Nurlaili (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Family food security in rural areas depends, in part, on the availability of animal protein sources from raising free-range chickens. However, simple cages that do not implement animal welfare principles can limit livestock productivity. This study aims to develop and evaluate the Happy Chicken Coop innovation based on animal welfare through community empowerment in Randuagung Village, Singosari District, Malang Regency. The study used the Research and Development (R&D) method with the ADDIE model and involved 25 Superior Free-Range Chicken Farmers (KUB) through saturated sampling. In the Development stage, the product was validated by livestock and construction experts and tested. The Implementation stage was carried out through the application of the cage by the community and measurement of user responses, while the Evaluation stage assessed community acceptance based on Rogers' innovation diffusion indicators. Data were collected using a 1–4 Likert scale questionnaire and analyzed descriptively quantitatively. The results showed a need for innovation of 76.51%, validation by livestock experts of 83.33%, construction experts of 87.50%, and product trials of 90%. User response reached 78.75%, while community acceptance was 90.45%. The findings indicate that the Happy Chicken Coop is feasible and acceptable as an appropriate technology based on community empowerment that has the potential to support family food security in a sustainable manner